Homoeopathy Industry Forging Ahead (Homoeopathy for All, 2022)
Homoeopathy as a scientific system of medicine has been growing ever since its inception and always for the better. The concepts, the principles as taught by our master still stand undeterred and so do the results, if the prescription is right. Here comes the role of manufacturing industry who actually processes the raw materials to deliver a quality product to be used by the end user, our patient. We have seen that commercial and bulk requirements of medicines at a large scale, to cater to the demand of industry, do require high end machines as well as quality testing to finally yield a standard product. To be able to achieve this, stringent norms have to be followed for procurement of raw material, packaging as well as on floor SOP for consistent quality and lab testing at all levels to mark the specific check parameters for each product to counter any misbranded or similar acting products or related products which may have similar action but not the right one.
Keywords: medicine; procurement; industry